Stress-strain curves for wire arc additively manufactured steels. (15th March 2023) - Huang, Cheng; Kyvelou, Pinelopi; Gardner, Leroy
Highlights: Existing stress–strain models for conventional structural steels are reviewed. Constitutive models are proposed to represent stress–strain curves of WAAM steels. Over 600 experimental stress–strain curves on WAAM steels are collected and analysed. Predictive expressions or values for the required input parameters are developed. Accuracy of model demonstrated through comparisons with measured stress–strain curves. Abstract: Interest in the use of wire arc additive manufacturing (WAAM) in construction has increased rapidly in recent years. Key to facilitating wider application is an improved understanding of the material behaviour. In particular, with structural design by finite element analysis in mind, constitutive models to describe the full range stress-strain response of WAAM steels are needed; development of such models is the focus of the present study. WAAM normal-strength steels generally exhibit a stress-strain response featuring a well-defined yield point, a yield plateau (for machined material) or slightly inclined yield plateau (for as-built material) and subsequent strain hardening, while the stress-strain response of WAAM high-strength steels is typically rounded, with no distinct yield point or plateau. This behaviour is similar to that of conventionally-produced steels, and hence can be represented analytically using existing material models, but with suitable modifications — a quad-linear or bilinear plus nonlinear hardening model and a two-stage Ramberg-Osgood model are proposed for WAAM normal- and high-strength steels, respectively. Predictive expressions or standardised values for the input parameters required in the models are developed and calibrated against a comprehensive database of WAAM steel coupon test results collected from the literature. The experimental database comprises over 600 engineering stress-strain curves and covers different feedstock wires, surface finishes (i.e. machined and as-built), material thicknesses, directions of testing and printing strategies. The proposed material models are shown to accurately predict the full stress-strain curves of WAAM steels, and are considered to be suitable for incorporation into analytical, numerical and design models for WAAM steel structures.